On the Role of Teacher-Student Rapport on English as a Foreign Language Students’ Well-Being - Li, Sa (Frontiers in Psychology, 2022)
Given the centrality of EFL students’ wellbeing in their academic success, identifying factors that may be influential in fostering students’ well-being is of high importance. As such, several studies have delved into the role of various personal and interpersonal factors in increasing EFL students’ well-being. However, little attention has been devoted to the function of teacher-student rapport. Besides, no systematic or theoretical review has been conducted in this regard. To address these gaps, the present study intends to illustrate different definitions of student well-being and teacher-student rapport, their sub-components, and their theoretical relations. Building upon the theoretical and empirical bases, the facilitative function of teacher-student rapport in increasing EFL students’ well-being was proved. Some beneficial implications are also discussed.